Uso da glicose e sucção não nutritiva no alívio da dor em neonatos - Lima, Alanna Gleice Carvalho Fontes (2015)
Pain is a relevant clinical significance phenomenon, however little evaluated and treated, especially among newborns. This population is subjected to painful procedures within the first hours of life, and no analgesic measure is implemented. The objective of this study was to compare the analgesic effect of glucose 25% and non-nutritive sucking in newborns undergoing vaccination against hepatitis B. The hypothesis is that non-pharmacological methods (glucose 25% and non-nutritive sucking) are effective in relieving Pain. This is a randomized controlled trial, consisting of three groups: 25% glucose, non-nutritive sucking and control. A total of 120 neonates were eligible for the study. Born with mean gestational age of 39 ± 0.9 weeks and were undergoing immunization against hepatitis B. For quantification of pain it used the Pain Scale in the Newborn (NIPS-Brazil). The primary endpoint was the this scale pain score and the secondary endpoint was duration of crying time, this recorded between the start of immunization to 180s after completion of the procedure. The NIPS score was statistically significant in all three groups, the score being less than four, the glucose group 25% (G25) 3.35 ± 2.1. The average crying time of the G25 group was 10.9 ± 11.3, and the average control group 52.7 ± 42.6. Glucose 25% showed greater efficacy in reducing pain when compared to non-nutritive sucking. There was a significant reduction in crying time in all groups, especially in the G25 group. It is suggested that the 25% glucose clinical practice be incorporated as a non-drug measure for pain relief during painful procedures.